Integrating Sustainability and Digitalization to Increase Profit in the Digital Age - Harri Romadhona; Zulfairah Zulfairah (Siber Nusantara Research, 2024)
The Role of Sustainability Integration and Digitalization to Increase Profit in the Digital Age is a scientific article of literature study within the scope of business management. The purpose of this article is to build a hypothesis that Sustainability Integration and Digitalization play a role in Increasing Profit in the Digital Age. The research object comes from online libraries such as Google Scholar, Mendeley, and other online academic media. The method used is library research, which is sourced from e-books and open access e-journals. The analysis is done descriptively qualitative. The results of this article show that: (1) The implementation of sustainability strategies plays a role in increasing company profits, and (2) The use of digital technology supports the implementation of sustainability in business.